2006
DOI: 10.1093/geront/46.3.391
|View full text |Cite
|
Sign up to set email alerts
|

Governance and Management Structures for Community Partnerships: Experiences From the Robert Wood Johnson Foundation's Community Partnerships for Older Adults Program

Abstract: Community partnerships for older adults can become influential positive forces but must invest in adequate governance and management structures early on.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 2 publications
0
17
0
Order By: Relevance
“…To address issues of accessibility, availability, affordability, and quality of community-based long-term care and services, the Robert Wood Johnson Foundation has initiated the program Community Partnerships for Older Adults with the focus on improving local service-delivery infrastructure. One of the strategies of local community partnerships is to increase awareness about long-term care and services within the community, specifically awareness of resources, access points, eligibility, and insurance coverage (Bolda et al, 2006). This study also indicated that perceived awareness of availability of various community services was associated with the likelihood of agingin-place and relocation anticipations.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…To address issues of accessibility, availability, affordability, and quality of community-based long-term care and services, the Robert Wood Johnson Foundation has initiated the program Community Partnerships for Older Adults with the focus on improving local service-delivery infrastructure. One of the strategies of local community partnerships is to increase awareness about long-term care and services within the community, specifically awareness of resources, access points, eligibility, and insurance coverage (Bolda et al, 2006). This study also indicated that perceived awareness of availability of various community services was associated with the likelihood of agingin-place and relocation anticipations.…”
Section: Discussionmentioning
confidence: 64%
“…As an initiative of the Robert Wood Johnson Foundation, the CPFOA was aimed at improving long-term care and supportive service systems for older adults through sustaining local community-based partnerships. The local community was composed of older adults, health and social service providers, Area Agencies on Aging, government and business leaders, and local funders (Bolda et al, 2006). The survey was part of the evaluation of the CPFOA program, which was designed to identify older adults at risk of needing long-term care and assess gaps in their knowledge about the options available (Black & Brown, 2004 Households in these communities were selected using list-assisted random digit-dialing, and one respondent from each eligible household was randomly selected (Black & Brown, 2004).…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, efforts are needed to strengthen and modernize the current education and information networks with the emphasis on targeting older adults, their caregivers, and professionals; establishing linkage to resources; and developing communication infrastructure (Lawler and Berger 2009). Since people are likely to turn to a variety of sources for information, efficient community partnerships will ensure the reliability of information and easy access to community services (Bolda et al 2006). Various social support resources will promote aging in…”
Section: Resultsmentioning
confidence: 99%
“…Examples include terms such as community partnerships (Bolda et al, 2006), community coalitions (Foster-Fishman et al, 2001), policy communities (Rhodes, 1997) and collaborative governance (Huxham, 2000). These terms include a range of relationships and modes of inter-dependence, and incorporate a continuum of relationships (Lawson et al, 2006; for a review, see Warburton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%